A cross sectional study to evaluate the prevalence of cardiovascular risk factors among college students aged 18-25 years in and around Calicut - Premlal, K. S.; Bhanushali, Vasantkumar V.; Nagalingam, Saranya (International Journal Of Community Medicine And Public Health, 2018)
Background: Cardiovascular disease (CVD) has a major impact on both developed and developing nations as it has become as a leading cause of death all over the World. In recent years an increasingly robust body of epidemiological evidence has highlighted the proliferation of CVD risk factors worldwide. The westernization of dietary habits, decreased levels of physical activity, increased childhood obesity and increased tobacco consumption accelerated by industrialization, globalization now threaten once low risk regions. The project aims to establish the need for screening, risk assessment, education and management in young adults. Objective of the study was to assess the risk behaviours in relation to smoking habits, alcohol use, sexual promiscuity among college going youth populace in southern part of Calicut. Methods: A cross-sectional study was conducted among college students aged 18-25 years around Calicut city. Study was conducted during the months of June 1st and July 30th 2016. The colleges were selected using simple random sampling method and the partakers were interviewed after getting assent from the concerned institutions. The sample size was calculated as 200 from WHO Global health observatory data prevalence of tobacco usage as 51%. Results: Mean (SD) age of study population is 20.90 (±2.11). Majority of the study population were females (78.5%) and males were 21.5%. Prevalence of smoking found to be 4% and alcohol consumption was found to be 2.5% among study population. BMI of the study population is 21.04 (±3.73). Conclusions: The results of this survey are alarming that the college going youth population fail to understand the devastating consequences of risky behaviours. Hence, interventions must be designed to prevent high-risk behaviours among the vulnerable population.